Modulation bandwidth, noise, and stability of a semiconductor laser subject to strong injection locking - Liu, J.M.; Chen, H.F.; Meng, X.J.; Simpson, T.B. (IEEE photonics technology letters, 1997)
Operating conditions for modulation bandwidth enhancement, noise reduction, and stable locking to be simultaneously fulfilled in a semiconductor laser subject to strong optical injection are investigated. When the strength of the injection signal is fixed, the optimum detuning of the injection frequency exists as a tradeoff between bandwidth enhancement and noise reduction. When the laser is injection-locked at a given value of frequency detuning in the stable locking region, both bandwidth enhancement and noise reduction are improved as the injection parameter is increased over a wide range.